3-D Digital Signature based on SHA-AES-ECC Scheme using Galois Field over GF(2n) - Amjad, Mohammad; Arora, Aman (International Journal of Computer Sciences and Engineering, 2020)
Approaches of handwritten signatures is no longer adequate for protection with the development of Internet technology, so the modern technique called digital signature has emerged. Digital signature is more typically used as term encompassing only cryptographic signatures. Digital signatures are mainly used in the delivery of financial transfers, certificates and applications, where the prevention of forgery or tampering of data is crucial. But even within digital signature, there are cryptographic techniques like AES, SHA and asymmetric enciphering mechanism such as ECC combined together to make it highly secure, used three steps mechanism of generation and verification called as 3-D signature. This research paper discusses the combination of all three modes of security such as Symmetrical, Hashing and Asymmetrical cryptography to make the digital signature more secure and invulnerable to attack. The simulation results shows that the proposed 3-D digital signature scheme along with Galois Field is suitable for used in real time environment like IoT, WSN, Cloud computing and low memory devices such as smart cards. The proposed technique is based on mathematical model used in SHA-AES-ECC with Galois Field GF(2n) with irreducible polynomial. Python Programming language is used to grasp the method used.